2020
DOI: 10.1002/sctm.19-0418
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from P2X7 receptor gene-modified cells rescue inflammation-compromised periodontal ligament stem cells from dysfunction

Abstract: Although cellular therapy has been proposed for inflammation-related disorders such as periodontitis for decades, clinical application has been unsuccessful. One explanation for these disappointing results is that the functions of stem cells are substantially compromised when they are transplanted into an inflammatory in vivo milieu. Considering the previous finding that P2X7 receptor (P2X7R) gene modification is able to reverse inflammation-mediated impairment of periodontal ligament stem cells (PDLSCs), we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 63 publications
(140 reference statements)
0
21
0
Order By: Relevance
“…Dysbiosis in the periodontal cavity promotes the growth of pathogenic microbiota such as Porphyromonas gingivalis and Fusobacterium nucleatum , contributing to autoantibody generation and subversion of host immune responses after invasion of these autoantibodies into the circulatory system and various organs [ 63 ]. Xu et al demonstrated that exosomes from P2 × 7 receptor (P2 × 7R) gene-modified periodontal ligament stem cells (PDLSCs) restored the compromised regenerative function of neighboring cells by binding to the GREM-1 protein and upregulating the expression of miRNAs including miR-3679-5p, miR-6515-5p, and miR-6747-5p [ 64 ]. Exosomal microRNA-155-5p from PDLSCs directly rectified the imbalance in the Th17/Treg ratio by regulating the expression of sirtuin-1 (SIRT1) in a chronic periodontitis experimental model [ 65 ].…”
Section: Immune-related Diseasesmentioning
confidence: 99%
“…Dysbiosis in the periodontal cavity promotes the growth of pathogenic microbiota such as Porphyromonas gingivalis and Fusobacterium nucleatum , contributing to autoantibody generation and subversion of host immune responses after invasion of these autoantibodies into the circulatory system and various organs [ 63 ]. Xu et al demonstrated that exosomes from P2 × 7 receptor (P2 × 7R) gene-modified periodontal ligament stem cells (PDLSCs) restored the compromised regenerative function of neighboring cells by binding to the GREM-1 protein and upregulating the expression of miRNAs including miR-3679-5p, miR-6515-5p, and miR-6747-5p [ 64 ]. Exosomal microRNA-155-5p from PDLSCs directly rectified the imbalance in the Th17/Treg ratio by regulating the expression of sirtuin-1 (SIRT1) in a chronic periodontitis experimental model [ 65 ].…”
Section: Immune-related Diseasesmentioning
confidence: 99%
“…GRPR, a gastrin-releasing peptide receptor, has been reported to be involved in the healing process in the synovium in patients with OA (Grimsholm et al, 2008). Xu et al (2020) demonstrated that miR-6515-5p was highly expressed in P2 × 7R gene-modified stem cell-derived exosomes and reduced inflammation-mediated impairment of periodontal ligament stem cells through indirect binding to the GREM-1 protein. Together with our results, we speculate that exosomes isolated from human BMSCs may regulate chondrocyte growth by the LYRM4-AS1/GRPR/miR-6515-5p signal axis, reducing inflammation in OA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the gene modification of the P2X7 receptor (P2X7R) can promote the repair of inflammatory lesions in PDLSCs. In addition to maintaining their robust functionality under inflammatory conditions, P2X7R gene-modified stem cells may have positive influences on their neighbors through paracrine mechanism, suggesting a novel strategy to modify the harsh local microenvironment of periodontitis to accommodate stem cells and promote improved tissue regeneration (206).…”
Section: Gene Therapymentioning
confidence: 99%